Belimumab for Immune-Mediated Necrotizing Myopathy Associated With Anti-SRP Antibodies: A Case Report and Retrospective Review of Patients Treated With Anti-B-Cell Therapy in a Single Center and Literature - Cui, Bei-Bei; Tian, Yun-Ru; Ma, Xin-Yue; Yin, Geng; Xie, Qibing (Frontiers in Immunology, 2021)
Background Immune-mediated necrotizing myopathy (IMNM) is characterized by markedly elevated creatinine kinase and histologically scattered necrotic muscle fibers and generally associated with autoantibodies against signal recognition particle (SRP) or 3-hydroxy-3-methylglutaryl-coA-reductase (HMGCR). Poor clinical response to conventional therapies and relapses commonly occur in severe cases. Anti-B-cell therapies have been used in refractory/relapsing cases. Methods The characteristics of a patient with IMNM associated with anti-SRP antibodies including physical examination, laboratory tests, and disease activity assessment were evaluated. Conventional therapy, belimumab treatment schedule, and follow-up data were recorded. Medical records of IMNM patients treated in our department from September 2014 to June 2021 were reviewed to evaluate the efficacy and safety of anti-B-cell therapy for anti-SRP IMNM. A literature review of patients with anti-SRP IMNM treated with anti-B-cell therapies was performed. Results We describe a case of a 47-year-old woman with IMNM associated with anti-SRP antibodies who relapsed twice after conventional therapy but showed good response and tolerance to belimumab at 28 weeks follow-up. In this review, three patients from our department were treated with rituximab. Two of the three patients rapidly improved after treatment. Twenty patients and five retrospective studies were included in the literature review. All patients were administered rituximab as an anti-B-cell drug. Conclusion Despite a lack of rigorous clinical trials, considerable experience demonstrated that anti-B-cell therapy might be effective for patients with IMNM associated with anti-SRP antibodies. Belimumab in association with steroids might be an encouraging option for refractory/relapsing cases.